Evaluation of coupled SWAT-MODFLOW-NWT model for conjunctive use of surface water and groundwater resources in the Mahabad plain of Iran - Omid Raja; Masoud Parsinejad; Massoud Tajrishy (Scientific Reports, 2024)
Abstract The Urmia Lake Basin has been severely affected by the unbalanced exploitation of water resources. To better manage the use of integrated water resources, the coupled SWAT-MODFLOW-NWT was adopted for the Mahabad Plain in the Urmia Lake Basin, N.W. Iran. The results indicated that a multifunctional calibration of SWAT and MODFLOW-NWT hydrological models in a large-scale irrigated area was necessary, using parameters such as evapotranspiration and crop yield in addition to the usual surface runoff and water table measures. The coupled model was then used to evaluate several water allocation scenarios, such as alternate proportions of irrigation water allocation from conjunctive water resources. The ultimate objective of adopting these scenarios was to increase the residual share of the water supply in order to compensate for the deprived share of Urmia Lake. The results of this study demonstrated that that the coupled SWAT-MODFLOW-NWT model was able to satisfactorily simulate the surface and groundwater balance components at different spatial and temporal dimensions. The results indicate that the Mahabad aquifer is capable of supplying irrigation water needs in the central and northern regions, with some limitations around running rivers. Furthermore, groundwater sustainability indicators showed that even with an additional 30% of the water supply from groundwater, the long-term sustainability of groundwater resources was preserved Ultimately, the findings indicated that a reduction in water allocation from surface waters can lead to an increase in water release to the lake of 16 million cubic meters (21%) to 18 million cubic meters (25%) in different years. The outcomes of this study can serve as a guiding principle for the optimal and sustainable allocation of surface and groundwater resources in highly competitive and fragile basins such as Lake Urmia.